2012
DOI: 10.4081/ija.2012.e37
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of metal nanoparticles in living plants

Abstract: In recent years, nanotechnologies have evolved from a multidisciplinary research concept to a primary scientific field. Rapid growth of new technologies has led to the development of nanoscale device components, advanced sensors, and novel biomimetic materials. In addition to chemical and physical approaches a new, simple and cheaper strategy to synthesize metal nanoparticles utilizes biological tools such as bacteria, yeasts, fungi, and plants. The majority of research has investigated ex vivo synthesis of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(54 citation statements)
references
References 64 publications
1
52
0
1
Order By: Relevance
“…These can be applied in food and other packaging, construction, and transportation vehicle body structures. Nanofertilizer, nanopesticides including nanoherbicides, nanocoating, and smart delivery system for plant nutrients are being used extensively in agriculture with several industries making formulations which contain 100-250 nm nanoparticles that are more soluble in water thus increasing their activity [39]. Nanofertilizers are able to synchronize the release of nutrients with their plant uptake, thus avoiding nutrient losses and reducing the risks of groundwater pollution.…”
Section: Agricultural Engineeringmentioning
confidence: 99%
“…These can be applied in food and other packaging, construction, and transportation vehicle body structures. Nanofertilizer, nanopesticides including nanoherbicides, nanocoating, and smart delivery system for plant nutrients are being used extensively in agriculture with several industries making formulations which contain 100-250 nm nanoparticles that are more soluble in water thus increasing their activity [39]. Nanofertilizers are able to synchronize the release of nutrients with their plant uptake, thus avoiding nutrient losses and reducing the risks of groundwater pollution.…”
Section: Agricultural Engineeringmentioning
confidence: 99%
“…This yields NPs for industrial use by growing plants in defined soils (Marchiol, 2012). For example, research has shown that alfalfa plants grown in gold rich soil absorb gold NPs through their roots and accumulates them in their tissues (Gardea-Torresdey et al, 2002).…”
Section: Applications Of Nanotechnology In the Agricultural Sectormentioning
confidence: 99%
“…It is probably notable to indicate that nanoparticle synthesis of gold, silver, and copper in particular has been observed and studied in a number of biomimetic or "green" synthesis regimes including bacteria (Anastas and Warner 2000), fungi (Ahmad et al 2003), and plants, where plant components uptake metal ions from the soil and produce small, colloidal, or neutral nanogold, copper, or silver crystals or polycrystal forms (MarChiol 2012;Das and Marsili 2010). In these processes the reduced, neutral metal nanoparticles can be recovered by simple combustion of the organic matrix.…”
Section: Introductionmentioning
confidence: 99%